A serological survey of echinococcosis, toxocariasis and trichinellosis among rural inhabitants of Central Yakutia. Issue 1 (1st January 2019) - Nakhodkin, Sergey S.; Pshennikova, Vera G.; Dyachkovskaya, Paraskovia S.; Barashkov, Nikolay A.; Nikanorova, Alena A.; Teryutin, Fedor M.; Melnichuk, Olga A.; Crubézy, Eric; Fedorova, Sardana A.; Magnaval, Jean-François
ABSTRACT: In 2018, a seroepidemiological survey was carried out in 3 ulus, or districts (Churapchinsky, Megino-Kangalassky and Ust-Aldansky) in Central Yakutia (Sakha Republic, Russian Federation) about 3 helminth zoonoses, namely, echinococcosis (alveolar or cystic), toxocariasis and trichinellosis. Ninety rural volunteers agreed to answer a questionnaire that inquired about demographic and environmental parameters along with food habits. Then they were asked to provide a venous blood sample. Serological investigations were carried out by enzyme-linked immunosorbent assay. Four subjects tested positive for echinococcosis, 1 for toxocariasis and 2 for trichinellosis. No demographic or environmental or dietary possible risk factor was found to be associated with these positive results. In conclusion, only echinococcosis and trichinellosis appeared to be in Yakutia as health threats among the 3 investigated zoonoses.